New Social Media and Politics in Thailand: the Emergence of Fascist Vigilante Groups on Facebook - Schaffar, Wolfram (2016)
Abstract: Since 2010, Facebook has become a battleground between competing political camps in Thailand. Facebook groups like the Social Sanction group, tellingly abbreviated as SS, and the Rubbish Collector Organization, which was founded in 2014 and has attracted more than 200,000 members, have played a crucial role in the process of political radicalization. The aim of these groups is to expose political opponents by accusing them of lèse-majesté, which can result in a prison sentence of 15 years or more. The groups also serve as fora for hate speech and are increasingly used as a tool of mobilization for state-sponsored mass events by the authoritarian regime that came to power with the coup d’état of May 2014. Contrary to its popular perception as a tool for democratization, Facebook has been successfully used by political groups reminiscent of fascist vigilante groups. This paper analyses the genesis of these groups and discusses the phenomenon in a broader political and historical cont